Measuring Noseband Tightness on the Lateral Aspect of the Horse’s Face - Russell MacKechnie-Guire; Hilary Clayton; Jane Williams; David Marlin; Mark Fisher; Diana Fisher; Victoria Walker; Rachel Murray (Animals)
Measuring tools designed to objectively determine equine noseband tightness are inserted on the dorsal nasal planum in a rostro-caudal direction. The lateral aspect of the horse’s head has several areas where minimal soft tissue intervenes between the skin and underlying bone, which makes them potentially useful sites for measuring noseband tightness. One hundred horses were fitted with a snaffle bridle with a cavesson, Swedish or dropped noseband in random order. The tightness of each noseband type was adjusted sequentially to 2.0, 1.5, 1.0, 0.5 and 0.0 finger-equivalents using an ISES Taper Gauge. For each adjustment, a digital calliper determined the distance (mm) between the inner surface of the noseband at three lateral locations: (1) lateral nasal bone, (2) lateral maxilla rostral to the facial crest, and (3) lateral mandible. Friedman’s analysis was used to test the differences between locations (p < 0.02). No differences were found between 2.0 and 1.5 finger-equivalent tightness at the nasal and maxillary sites for the cavesson (p = 0.89, p = 0.03, respectively) and Swedish (p = 0.06, p = 0.40, respectively) noseband. When adjusted between 2.0 to 0.5 finger-equivalent tightness, the coefficient of variation was “good” for the nasal (16%) and maxilla (19%) sites. These results indicate that a lateral measuring site may provide a suitable addition to dorsal midline measurements.